New records of Anastrepha (Diptera: Tephritidae) from Paraguay - Rodriguez, Pedro Alexander Clavijo; Miret, Luz Maria; Norrbom, Allen L.; Garay, Liz Carolina; Coronel L., Blanca E.; Peñaranda, Emilio Arévalo (Zootaxa, 2020)
This work presents new distribution records in Paraguay for 19 fruit fly species of the genus Anastrepha Schiner, including four new records for the country: A. alveatoides Blanchard, A. australis (Blanchard), A. obliqua (Macquart) and A. pastranai Blanchard. Additionally, an updated list of the 26 Anastrepha species present in Paraguay is provided, as well as illustrations (wings, aculeus tips) of the majority of species.